2022
DOI: 10.3390/su14148505
|View full text |Cite
|
Sign up to set email alerts
|

Creating Shared Value: Exploration in an Entrepreneurial Ecosystem

Abstract: The effects of companies on society and the practices of Corporate Social Responsibility have been the source of interest for many research studies. Questions concerning the traditional model resulted in Porter and Kramer developing the concept of Creating Shared Value, an approach where companies consider the value of society and the environment in their business models, creating value for all stakeholders. We take the issue of shared value creation in an entrepreneurial ecosystem to determine how clustered c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 117 publications
0
12
0
Order By: Relevance
“…Enterprises with CSV strategies increase the value of clusters by sharing knowledge and providing information resources (Marsé et al, 2015; Royo‐Vela & Cuevas, 2022). There is a strong spillover effect on enterprises providing information resources.…”
Section: Additional Analysesmentioning
confidence: 99%
“…Enterprises with CSV strategies increase the value of clusters by sharing knowledge and providing information resources (Marsé et al, 2015; Royo‐Vela & Cuevas, 2022). There is a strong spillover effect on enterprises providing information resources.…”
Section: Additional Analysesmentioning
confidence: 99%
“…Second, not only companies and customers, but also public actors, communities and territories that co-create value and benefit from it are in focus. This concept of value that entails the simultaneous pursuit of socio-economic benefits by and for multiple actors reflects the definition of shared value in IEs (Alberti and Belfanti, 2019; Arena et al ., 2021; Royo-Vela and Cuevaz-Lizama, 2022), which is defined as capable of enhancing “ the competitiveness of a company while simultaneously advancing the economic and social conditions in the communities in which it operates ” ' (Porter and Kramer, 2011, p. 66), through properly set policies and practices. The domain of benefits generated by policies and practices fostering shared value can even extend to economic, social and environmental ones, in line with the TBL framework.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Royo-Vela and Cuevas Lizama (2022) observed that shared value can be created through the relationships among companies and other actors: companies co-create value with these entities, benefitting themselves and the actors comprising the ecosystem by reaching TBL outputs. Indeed, an IE is comprised of independent actors who are the constituent nodes of the IE itself: they have diverse characteristics, needs, resources and capabilities and aggregate in an IE becoming interdependent but remaining independent (Ritala and Almanopoulou, 2017; Jacobides et al ., 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In that sense, the model proposed in this paper comprises the economic, social, and environmental dimensions proposed by Porter and Kramer (2011) and the results in those dimensions that were indicated in subsequent research (Porter et al, 2012). Similarly, based on previous qualitative analysis and literature review we identified two dimensions that contemplate external and internal conditions that influence CSV adoption (Royo-Vela & Cuevas-Lizama, 2022;Menghwar & Daood, 2021;Mühlbacher & Böbel, 2019). External conditions such as state institutions, customer behavior, and competitors' strategies affect firms' adoption of social and environmental strategies (Menghwar & Daood, 2021).…”
Section: Introductionmentioning
confidence: 99%